Elimination of quinolone antibiotic carryover through use of antibiotic-removal beads. - Zabinski, R A (1993)
To prove the utility of antibiotic-removal beads in separating antibiotics from bacterial samples, Escherichia coli ATCC 25922 was exposed to five separate quinolones before and after each was exposed to antibiotic-removal beads. Plates treated with antibiotic solutions that were exposed to beads demonstrated antibiotic removal, and plates treated with antibiotic solutions that were not exposed to beads demonstrated antibiotic carryover. After exposure to beads, fluoroquinolone concentrations decreased from 5 micrograms/ml to 0.14 micrograms/ml (ciprofloxacin), 0.04 micrograms/ml (temafloxacin), < 0.01 microgram/ml (ofloxacin), < 0.01 microgram/ml (sparfloxacin), and 0.02 micrograms/ml (clinafloxacin). These data indicate that antibiotic carryover can be successfully circumvented through the use of antibiotic-removal beads.